Proceedings of the 14th Annual ACM SIGCSE Conference on Innovation and Technology in Computer Science Education 2009
DOI: 10.1145/1562877.1562930
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of a relationship between explaining, tracing and writing skills in introductory programming

Abstract: This paper reports on a replication of earlier studies into a possible hierarchy of programming skills. In this study, the students from whom data was collected were at a university that had not provided data for earlier studies. Also, the students were taught the programming language "Python", which had not been used in earlier studies. Thus this study serves as a test of whether the findings in the earlier studies were specific to certain institutions, student cohorts, and programming languages. Also, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…There is a stronger relationship between code comprehension and debugging than between code writing and debugging [12,15,16]. The students are more confident in writing when they have better knowledge and debugging skills [17].…”
Section: Competencies Skills and Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…There is a stronger relationship between code comprehension and debugging than between code writing and debugging [12,15,16]. The students are more confident in writing when they have better knowledge and debugging skills [17].…”
Section: Competencies Skills and Curriculummentioning
confidence: 99%
“…Some studies showed that the students mastered the debugging skills developed better code writing skills [12,15,16]. The character metaphor as a variable state helps to improve together the debugging and writing skills.…”
Section: ) Which Are the Abilities And Topics Covered By These Games?mentioning
confidence: 99%
“…At the highest level, evaluation, were placed those strategies indicating analysis for deeper meaning. This foreshadows the work of Lister, Fidge, and Teague [28], which identified the explaining of code's problem-solving purpose as different from understanding at a lineby-line level.…”
Section: Educational Taxonomies In Programmingmentioning
confidence: 96%
“…This work was built upon in a further study in which Lister, Fidge, and Teague [28] found that effective programmers had developed good tracing skills prior to good writing skills, and that good students can explain the purpose of code without stating what it does line by line. This led them to conclude that writing good effective code requires both tracing and explaining skills [28].…”
Section: Teaching Programmingmentioning
confidence: 98%
See 1 more Smart Citation